Interface modiﬁcation of clay and graphene platelets reinforced epoxy nanocomposites: a comparative study - Zaman, Izzuddin; Manshoor, Bukhari; Khalid, Amir; Meng, Qingshi; Araby, Sherif (Springer International Publishing, 2014)
The interface between the matrix phase and dispersed phase of a composite plays a critical role in inﬂuencing its properties. However, the intricate mecha-nisms of interface are not fully understood, and polymer nanocomposites are no exception. This study compares the fabrication, morphology, and mechanical and thermal properties of epoxy nanocomposites tuned by clay layers (denoted as m-clay) and graphene platelets (denoted as m-GP). It was found that a chemical modiﬁcation, layer expansion and dispersion of ﬁller within the epoxy matrix resulted in an improved interface between the ﬁller mate-rial and epoxy matrix. This was conﬁrmed by Fourier transform infrared spectroscopy and transmission electron microscope. The enhanced interface led to improved mechanical properties (i.e. stiffness modulus, fracture toughness) and higher glass transition temperatures (Tg) compared with neat epoxy. At 4 wt% m-GP, the critical strain energy release rate G1c of neat epoxy improved by 240 % from 179.1 to 608.6 J/m2 and Tg increased from 93.7 to 106.4 C. In contrast to m-clay, which at 4 wt%, only improved the G1c by 45 % and Tg by 7.1 %. The higher level of improvement offered by m-GP is attributed to the strong interaction of graphene sheets with epoxy because the covalent bonds between the carbon atoms of graphene sheets are much stronger than silicon-based clay.